The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.1128/jb.140.1.167-181.1979
|View full text |Cite
|
Sign up to set email alerts
|

Transposon A-generated mutations in the mercuric resistance genes of plasmid R100-1

Abstract: A series of 23 transposon 801(Tn801)-induced mutations of plasmid R100-1 from mercuric salts resistance to sensitivity was studied. Although Tn801 transposed frequently into the mer region of the plasmid, fine structural analysis showed that the site of insertion within mer varied. About one-half of the Tn801 insertion events also caused a deletion of greater than 1 megadalton. Genetic and restriction endonuclease EcoRI and BamHI analysis of the mutant plasmid deoxyribonucleic acid elucidated the organization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
1

Year Published

1985
1985
2003
2003

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(65 citation statements)
references
References 44 publications
2
62
1
Order By: Relevance
“…This effect was not observed with either copC or copD expressed alone. Similar observations led to the discovery of a mercury transport system encoded by merT and merP associated with mercury resistance [30,31]. Preliminary uptake studies indicated that cells containing copCD accumulated more copper than cells without these genes or with either copC or copD alone [23].…”
Section: Cellular Copper Uptakementioning
confidence: 73%
“…This effect was not observed with either copC or copD expressed alone. Similar observations led to the discovery of a mercury transport system encoded by merT and merP associated with mercury resistance [30,31]. Preliminary uptake studies indicated that cells containing copCD accumulated more copper than cells without these genes or with either copC or copD alone [23].…”
Section: Cellular Copper Uptakementioning
confidence: 73%
“…Work on the mechanism of HgR led to identi¢cation of the key detoxi¢cation enzyme, MerA, the mercuric ion reductase [12], and also of a second enzyme, MerB, which split the carbon^Hg bond in such compounds as the disinfectant phenylmercuric acetate (PMA) and the fungicide methylmercury chloride, a potent neurotoxic agent [13]. Membrane and periplasmic proteins involved in the seemingly paradoxical inward transport of ionic mercury [14,15] were also identi¢ed [16,17]. The ¢rst sequences of HgR loci revealed proteins corresponding to these biochemical and physiological functions as well as a candidate regulatory gene (merR).…”
Section: A Brief History Of the Study Of Mercury Resistancementioning
confidence: 99%
“…The existence of an operon-speci¢c Hg(II) uptake system was ¢rst suggested on the basis of the Hg(II)-hypersensitive phenotype of merA mutants [14,15]; such variants were more sensitive to Hg(II) than cells lacking the operon altogether, consistent with there being some mechanism for bringing Hg(II) into the cell. In the absence of the mercuric reductase, the internalized Hg(II) is not de-toxi¢ed by reduction to Hg(q).…”
Section: Transportmentioning
confidence: 99%
“…Genetic analysis of the narrow-spectrum determinant of plasmid R100 revealed the following operon structure (8,14,16). A regulatory gene merR specifies a protein which controls transcription of the merTCA operon both positively and negatively.…”
mentioning
confidence: 99%
“…However, several observations suggest that the basic genetic organization might be quite similar to that of R100 or TnSOJ, with additional Hg2 -inducible genes specifying the organomercurial lyase subunits. (i) Plasmid R828, which specifies broad-spectrum Hgr, complemented a merR mutant of R100, stimulating induction of the mer operon (8).…”
mentioning
confidence: 99%